Electron transport through molecular wires based on a face-shared bioctahedral motif - Mistry, V; Georgiev, V; McGrady, J (2012)
Density functional theory in conjunction with non-equilibrium Green's functions is used to explore the electron transport properties of a series of molecules based on the face-shared bioctahedral (M 2Cl 9) motif. The metal-metal bond orders in the chosen molecules, [Rh 2Cl 9] 3-, [Ru 2Cl 9] 3- and [Mo 2Cl 9] 3- vary from 0 (Rh) to 1 (Ru) and 3 (Mo), and the calculations indicate that there is a direct correlation between conductance and bond order. The [Mo 2Cl 9] 3- case is particularly interesting as it is well known from crystallographic studies to be very flexible, the Mo-Mo bond length varying over a range of ∼0.35 depending on cation. The upper limit of this range marks the point where homolytic cleavage of the δ π components of the triple bond is complete, and this has a marked impact on electron transport. The localization of the metal-based orbitals means that those on the left (source) and right (drain) sides respond very differently to applied bias, giving rise to resonance effects at particular bias voltages, and hence to negative differential resistance effects. © 2011 Académie des sciences.